PENGARUH PRENATAL YOGA TERHADAP TINGKAT STRES PADA IBU SELAMA MASA KEHAMILAN - Sari, Febbi Wulan; Pramana, Yoga; Adiningsih, Berthy (ARCHIVE OF COMMUNITY HEALTH, 2024)
Changes that occur during pregnancy require good adaptation frompregnant women. The results of Regional Health Research state that the incidence of stress in Indonesia from 2017 to 2018 is estimated to have increased globally by around 10% in pregnant women. Stress that occurs in pregnant women has a bad impact on the baby they are carrying and has a bad impact on the mother. One of the solutions for dealing with stress in pregnant women is by doing yoga exercises. Objective of this study is to analyze the effect of prenatal yoga on stress levels in pregnant women.Method of this research is quantitative research using observational analytical cross sectional.sampling technique in this study used Total Sampling with 30 pregnant women respondents. Analysis of the data in this study using the Paired Sample T- Test. Result is the stress level of respondents before doing prenatal yoga was normal 40.0%, moderate stress was 33.3%, mild stress was 16.7%, severe stress was 10.0% and the stress level of respondents after doing prenatal yoga was normal 96.7% and mild stress by 3.3%. The statistical test showed a significant number between the pre-test values of prenatal yoga and post-test prenatal yoga with a significance value (2-tailed) p = 0.000, <0.05 there was a significant decrease in stress levels from 16.10 to 9.03 and the correlation coefficient value is 0.530 so it has a moderate relationship. Conclusion , there is an effect of prenatal yoga on stress levels in pregnant women during pregnancy Keywords: Prenatal Yoga, Pregnancy, Pregnancy Stress